Psychological ownership, territorial behavior, and being perceived as a team contributor: The critical role of trust in the work environment - Brown, Graham; Crossley, C.; Robinson, S. (2014)
In this field study, we develop and test a theory regarding the role of trust in the work environment as a critical condition that determines the relationship between psychological ownership, territoriality, and being perceived as a team contributor. We argue that, dependent upon the context of trust in the work environment, psychological ownership may lead to territorial behaviors of claiming and anticipatory defending and that, dependent upon the context of trust, territorial behavior may lead coworkers to negatively judge the territorial employee as less of a team contributor. A sample of working adults reported on their psychological ownership and territorial behavior toward an important object at work, and a coworker of each provided evaluations on the level of trust in the work environment and rated the focal individual's contributions to the team. Findings suggest that a work environment of trust is a "double-edged sword": On the one hand, a high trust environment reduces the territorial behavior associated with psychological ownership; on the other hand, when territorial behavior does occur in high trust environments, coworkers rate the territorial employee's contributions to the team significantly lower. We discuss the nature and management of territorial behavior in light of these findings. © 2013 Wiley Periodicals, Inc.